(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2019)
Apple storage under lower concentration of oxygen (1.0-1.3% in some cases lower than 1%) in controlled atmosphere cold stores is described as apple storage in ultra-low oxygen cold store. Ultra-low oxygen store room is an airtight gas cold room and its atmosphere is composed of lower rate of oxygen and higher amount of CO2. It has been Investigated and recorded that ultra-low oxygen cold store extends storage life of apple varieties (Royal Gala, Red Delicious, Idared, Jonagold and Golden delicious) from 3 to 6 months under common cold stores to 7-11 months with preserving its nutritional, sensorial and biological parameters and characteristics after harvest. For storage of apples in Afghanistan, mostly simple and cold storerooms are applied but inadequately and with local methods and facilities, due to application of ultra-low oxygen cold storage both can benefitfarmers, customers and economic growth of the country. Int. J. Agril. Res. Innov. & Tech. 9 (1): 18-22, June, 2019